LONGITUDINAL CHANGE IN LIVING ARRANGEMENTS AND COGNITIVE IMPAIRMENT. (20th December 2022) - Kim, Jiwon; Cantu, Phillip; Angel, Jacqueline
Abstract: Objective: To examine changes in living arrangements and cognition in the U.S. and Mexico. Methods: Latent class analysis to document the joint progression of cognitive impairment and changes in living arrangements using the Hispanic -EPESE and the Mexican Health and Aging Study (MHAS) Results: In the H-EPESE, vital status analyses reveal that those who died were more likely than survivors to report likely dementia and co-morbid physical conditions and one third of older adults lived alone. Almost one-fifth of the H-EPESE sample suffered a decline in cognition over time. Despite declines in cognitive function, there is a great deal of stability in living alone across waves. We expect even greater stability and change in living alone in the event of cognitive decline in the MHAS given cultural traditions and fewer options in care and a lower propensity to live alone in Mexico.